Transnational terrorism and the shifting paradigm of sovereignty: analyzing the Bokoharam counter terrorism - Qader, Mohammed Mustafa; Usman, Abbo; Masum, Ahmad; Abdul Rahman, Rohana (AENSI Publisher, 2015)
The historical backdrop of state sovereignty is portrayed by a consistent condition of progress. The inherent principles of sovereignty as enshrined in the treaty of Westphalia in 1648, such as the non-intervention, territorial integrity, and absolute power within the bounds of a state border, have been re-assessed over a long period of time in light of new difficulties to guarantee that they stay applicable to the needs of any given time.The very embodiment of sovereignty has constantly undergoes changes and adjustments to cope of with period of difficulties, ranging from the battle for minority rights to mixture of issues identifying with the new trendy expression of human rights and the obligation to maintain international peace and security.This paper, therefore, argues that contemporary states are showing a more prominent willingness to acknowledge compromises on matters of sovereignty in quest for a more effective counterterrorism motivation.States do not appear to be attaching an infinite value to sovereignty; yet rather consider it within the setting of broader national interest.In this way, the degree to which states effectively protect their sovereign prerogatives is subject to the same system as all other state decisions: the cost-benefit analysis.States measure the costs and benefits of any given policy or action and utilize the outcome as an aide for decision-making. In the present period, changing state demeanor s with respect to sovereignty and counter terrorism emerge from a shifting balance between costs and benefits in battling international terrorist groups.This evident with the establishment of a Multinational Joint Task Force which allows cross-border military operations by neighboring countries thereby creating a paradigm shift from the traditional and rigid conception of sovereignty to a more flexible one.